2016
DOI: 10.1681/asn.2015010062
|View full text |Cite
|
Sign up to set email alerts
|

Proteinuria as a Noninvasive Marker for Renal Allograft Histology and Failure

Abstract: Proteinuria is routinely measured to assess renal allograft status, but the diagnostic and prognostic values of this measurement for renal transplant pathology and outcome remain unclear. We included 1518 renal allograft recipients in this prospective, observational cohort study. All renal allograft biopsy samples with concomitant data on 24-hour proteinuria were included in the analyses (n=2274). Patients were followed for $7 years posttransplantation. Compared with proteinuria ,0.3 g/24 h, the hazard ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 30 publications
4
90
1
1
Order By: Relevance
“…Although the graft attrition rate at 1 year after transplantation has improved, it has not translated into a proportionate improvement in long-term renal graft survival [14, 15]. In recent years, specific diseases, such as antibody-mediated rejection and de novo/recurrent glomerular diseases, have been identified as the primary causes of renal graft failure [1518].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the graft attrition rate at 1 year after transplantation has improved, it has not translated into a proportionate improvement in long-term renal graft survival [14, 15]. In recent years, specific diseases, such as antibody-mediated rejection and de novo/recurrent glomerular diseases, have been identified as the primary causes of renal graft failure [1518].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, specific diseases, such as antibody-mediated rejection and de novo/recurrent glomerular diseases, have been identified as the primary causes of renal graft failure [1518]. The inability to prevent or treat these specific diseases is likely associated with the insufficient improvement in long-term renal graft survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study involving 33 patients, Kotanko et al found that paradoxically lower urNAG excretion is associated with reduced graft survival [24]. In a subsequent investigation, Ferdau et al demonstrate that urNAG level is positively associated with graft failure [13][14][15]. However, this predictive value disappeared when adjusted for albuminuria which had been demonstrated to be the best predictor of allograft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria has been established as a risk factor that confers poor outcome for a variety of kidney diseases both in the native kidneys and renal allografts [13][14][15]. Chronic endothelial injury and remodeling account for the main mechanism for proteinuria in TG, the severity of which as assessed by histologic score of cg does not necessarily correlated with proteinuria degree clinically, though.…”
Section: Discussionmentioning
confidence: 99%